The Role Of Source Credibility And Fairness On The Formation Of Parasocial Relationships And Product Interest And Their Influence On Purchase Intention And E-WOM Of Beauty Brands In Indonesia - Fadelia Dwiphala; Rifelly Dewi Astuti (Green Publisher Indonesia, 2024)
Few studies have focused on how source credibility and fairness influence parasocial relationships and product interest, and how product interest impacts consumers' purchase intentions towards new products. But few have examined how these factors can influence purchase intention and eWOM, so this study aims to fill the gap, focusing on Indonesian beauty influencers on Instagram. With 501 respondents, this study used SPSS 26 (pre-test) and SmartPLS for data analysis. The results show that: the variables of attractiveness, similarity, and trustworthiness have a significant and positive effect on parasocial relationships; similarity has a significant and positive effect on product interest. Interpersonal fairness and informational fairness have a positive and significant effect on parasocial relationships; and distributive fairness has a positive and significant effect on product interest. Parasocial relationship has a significant and positive effect on product interest, purchase intention, and eWOM. Product interest has a significant and positive effect on purchase intention and eWOM.